MANAJEMEN PARIWISATA RELIGI BERBASIS MODERASI BERAGAMA DI ISLAMIC CENTER MATARAM - Lalu Muhammad Saukad Rudi Gempar (Mudabbir: Jurnal Manajemen Dakwah, 2023)
This article discusses religious tourism at the Hubbul Wathan Mataram Islamic Center Mosque. As one of the largest centers for Islamic studies and civilization in Lombok, NTB, this mosque has never been absent from holding various religious and cultural activities, both regional and international, so that it is visited by many local and international tourists. One of the new programs being carried out is religious tourism based on religious moderation. This program aims to promote moderate religious concepts and interfaith harmony. From this background, this article will focus on discussing the issue of implementing religious tourism management functions based on religious moderation. Several important issues that will be answered in this article are, first, what is the religious moderation-based tourism program like? Second, how is the management of religious moderation-based tourism at the Hubbul Wathan Islamic Center mosque?. This article is the result of field research using a qualitative approach. While important data were obtained through field observations, in depth and structured interviews with administrators, and strengthened by documentation activities. This research shows that the management of religious moderation in the religious tourism program at the Islamic Center is packed with the provision of various facilities that can be used by everyone from different faith backgrounds, such as the use of a Ballroom, and the Islamic Center's masdi courtyard.